The European Degree - Sara Cardona Rubio (Quaderns IEE)
In 2024, the European Commission announced the latest development in the European Education Area: the European Diploma. The aim is to create a new type of qualification that will be automatically recognised throughout the EU. This project responds to various trends currently observed. For example, the consolidation of the knowledge economy; the need to achieve strategic autonomy; and the urgency of combating growing social inequalities, which contribute to creating polarised societies.